Towards a New Understanding of the Image of God in Genesis 1:26-27: An Analysis of the Constructions of the Verb ברא in the Hebrew Bible - van Wolde, Ellen (Journal of Hebrew Scriptures)

(untitled) (University of Alberta, 2026)
The article counters the common assumption that ברא (Qal) with the subject God means “to create” and the common rendering of humanity being “created in God’s image” in Gen 1:26-27. A number of scholars have expressed doubts about understanding ברא as “to create,” and concluded that ברא might be better understood in terms of separation or division. The present article builds on these arguments, extending them with an analysis of all verbal constructions of ברא (Qal) in the Hebrew Bible, and then proposes a new reading of Gen 1:26-27 based on this analysis.